Microbiome and microbial biofilm profiles of peri-implantitis: A systematic review (2017)
Background: This systematic review assesses microbiologic profiles of peri-implantitis, periodontitis, and healthy implants based on studies that evaluated microbial biofilms and entire microbiomes to establish their similarities and differences. Methods: The Medical Literature Analysis and Retrieval System Online via PubMed, Excerpta Medica Database, and Cochrane Central Register of Controlled Trials, were searched without language restrictions through July 30, 2016. Observational studies that evaluated microbial profiles or entire microbiomes of peri-implantitis compared with healthy implants or periodontitis were considered eligible for inclusion. A descriptive summary was created to determine quantity of data and interstudy variations. Results: Of 126 potentially eligible articles, 26 were included in this study. Twenty-one of these articles evaluated the microbiologic profile of peri-implantitis versus healthy implants or periodontitis using conventional microbiologic techniques. Five articles evaluated the entire microbiome using genomic sequencing. Teeth with periodontitis, healthy implants, or implants with peri-implantitis were colonized by periodontal microorganisms. Porphyromonas gingivalis and especially Prevotella intermedius/nigrescens were often identified at peri-implantitis sites. Peri-implantitis sites were also colonized by uncultivable asaccharolytic anaerobic Gram-positive rods and anaerobic Gram-negative rods, which were not frequently identified in teeth with periodontitis or healthy implants. Opportunistic microorganisms were not found very frequently in peri-implantitis sites. Conclusions: Peri-implantitis represents a heterogeneous mixed infection that includes periodontopathic microorganisms, uncultivable asaccharolytic anaerobic Gram-positive rods and other uncultivable Gram-negative rods, and, rarely, opportunistic microorganisms such as enteric rods and Staphylococcus aureus. Sequencing methods that evaluate the entire microbiome improve identification of microorganisms associated with peri-implantitis.